BENIGN MIXED EPITHELIAL TUMOR OF RENAL PELVIS; CASE REPORT - Muhammad Akram Malik; Nayab Alia (Journal of University Medical & Dental College)
ABSTRACT Cystic hamartoma of the renal pelvis is a rare benign tumour in same category as mixed epithelial & stromal tumor. We present a 37 year old female with a cystic lesion in renal pelvis, extending to pelvi-ureteric junction. She underwent nephrectomy. Histopathologically, tumour consisted of epithelial and mesenchymal cells and no evidence of malignancy. We believe that this is case of mixed epithelial and stromal tumours. The overall prognosis is good.